The 10-year functional outcome of schizophrenia in Butajira, Ethiopia - Kebede, Derege (Heliyon, 2019)
BACKGROUND: Long-term functional schizophrenia outcomes are not well characterized in low-income environments because of the rarity of prospective studies. OBJECTIVES: To assess and describe long-term schizophrenia's functional outcomes and potential outcome predictors. METHODS: Following a baseline assessment, 316 people with schizophrenia were studied for 10 years, on average. Of the total, 79 were incident cases: cases with onset of the illness occurring two years or less from entry into the study. SF-36 scores of physical and social functioning were used to assess functional outcomes. Linear mixed models were employed to evaluate the association of functioning with potential predictors. RESULTS: Social and physical functioning scores regarding the cohort were lower than the population's norm for most of the follow-up period. Incident cases had better function than prevalent cases. Fifteen percent of incident and 30% of prevalent cases had reduced social functioning for at least six years. Declining symptom severity during the follow-up period was significantly associated with improvement in social functioning. When baseline functioning was controlled for, the long-term trend in functionality was not associated with demographic or illness characteristics (age and speed of onset, duration of illness and neuroleptic use at entry, substance use, and medication adherence). CONCLUSION: Long-term physical and social functioning of the population with schizophrenia were significantly lower than the population norm. A significant proportion of the cohort had lower functioning for the long-term. Functioning was not associated with demographic or illness characteristics of the study population.